Răspuns :
110 - { 90 - 3 [ (9 a + 82 ) :4 + 16 ] : 10 : 3} = 87
90 - 3 [ (9 a + 82 ) :4 + 16 ] : 10 : 3 = 110 - 87 = 23
3 [( 9 a + 82 ) :4 + 16 ] : 10 : 3 = 90 - 23
3 × [ (9 a + 82 ) :4 + 16 ] : 10 : 3 = 67
3 × [ (9 a + 82 ) :4 + 16 ] : 10 = 67 × 3
3 × [ (9 a + 82 ) :4 + 16 ] : 10 = 201
3 × [ (9 a + 82 ) :4 + 16 ] = 201 × 10
3 × [ (9 a + 82 ) :4 + 16 ] = 2 010
(9 a + 82 ) :4 + 16 = 2 010 : 3
(9 a + 82 ) :4 + 16 = 670
(9 a + 82 ) :4 = 670 - 16
9 × a + 82 = 654 × 4
9 × a + 82 = 2 616
9 × a = 2 616 - 82
9 × a = 2 534
a = 2 534 : 9
a = 281,(6)
90 - 3 [ (9 a + 82 ) :4 + 16 ] : 10 : 3 = 110 - 87 = 23
3 [( 9 a + 82 ) :4 + 16 ] : 10 : 3 = 90 - 23
3 × [ (9 a + 82 ) :4 + 16 ] : 10 : 3 = 67
3 × [ (9 a + 82 ) :4 + 16 ] : 10 = 67 × 3
3 × [ (9 a + 82 ) :4 + 16 ] : 10 = 201
3 × [ (9 a + 82 ) :4 + 16 ] = 201 × 10
3 × [ (9 a + 82 ) :4 + 16 ] = 2 010
(9 a + 82 ) :4 + 16 = 2 010 : 3
(9 a + 82 ) :4 + 16 = 670
(9 a + 82 ) :4 = 670 - 16
9 × a + 82 = 654 × 4
9 × a + 82 = 2 616
9 × a = 2 616 - 82
9 × a = 2 534
a = 2 534 : 9
a = 281,(6)